Melanin system composition analyzed by XPS depth profiling - Paulin, J. V. [UNESP]; McGettrick, J. D.; Graeff, C. F.O. [UNESP]; Mostert, A. B. (Elsevier, 2021)
The melanins are a class of natural pigments ubiquitous throughout the biosphere. These pigments are gaining significant attention as advanced materials due to their biocompatibility, optical and electrical properties. The most common form of melanin, eumelanin, has a well-known problem of insolubility in most common solvents. The insolubility has made standard chemical analysis challenging, leading to researchers opting to use X-Ray photoelectron spectroscopy (XPS). However, standard XPS used on melanins and related materials have been limited to being a surface technique, and hence reported values to date may not reflect the bulk. In this work, we have investigated with XPS depth-profiling method the chemical information of the surface and the bulk of powder and thin-films of eumelanin and several melanin derivatives. These latter derivatives are modified melanins designed to overcome the insolubility of the standard systems. Our result indicates that there are only few differences in the chemical composition of the melanin chemical structure between the surface and bulk, for either the powder of film samples. Our results show that a basic surface probe is sufficient to obtain an accurate elemental composition for basic melanin samples. As such, our analysis indicates that XPS characterization is an important characterization of polyindolequinone systems in general such as the melanins and polydopamines.
Keywords: Depth-profile XPS, Polyindolequinone; Eumelanin; Melanin derivatives; Polydopamine; X-ray photoelectron spectroscopy